Work Posture Analysis of Musculoskeletal Disorders (MSDs) Complaints in MSME Workers Balloon Bouquet - Nurmaningsih Nurmaningsih; Widodo Hariyono; Muhammad Syamsu Hidayat (PROMOTOR, 2024)
It is known that MSDs have become a health problem for workers in developing and developed countries over the past few years. Musculoskeletal disease is the second leading cause of disability in the world, with low back pain being the leading cause of disability. If referring to this explanation, the activities of MSME workers, balloon bouquets that can potentially cause musculoskeletal complaints, one of which is the activity of pumping balloons manually and stringing balloons with awkward postures and carrying out work with a sitting work posture which causes musculoskeletal problems, especially shoulder & waist problems because there is pressure on the spine. The type of research used by the author in this study is the qualitative method. Qualitative research researchers become the main instrument in collecting data that can be directly related to the instrument or object of research. Data collection method using Rapid Upper Limb Assessment (RULA) observation sheet and Nordic Body Map (NBM) checklist sheet as well as interview guidelines. Workers often experience complaints of aches or pains both while working, and after doing work on the right shoulder, left shoulder, back, upper arm, forearm, and waist. The posture of workers when making a bouquet of balloons either when pumping, forming, or assembling balloons on average has a high risk level for complaints of musculoskeletal disorders because workers carry out work with a sitting, bending, squatting, and half-sitting work attitude, there are repetitive movements.